Re-Examining the Impact of Public Education Expenditure on South African Literacy - Muzekenyi Mike; Nyika Farai; Anyikwa Izunna; Kemda Lionel Establet (Economics and Business)
Much empirical literature has focused on investigating the role of government expenditure in promoting long-term economic growth in South Africa. However, few studies in comparison have considered the impact of government spending on literacy level in the country. To this end, this paper examines the impact of government spending on literacy rate in South Africa using an Autoregressive Distributed Lag (ARDL) model with annual time series data over the period from 1994 to 2021. The key findings of this study are: (a) there is evidence of a long run relationship between government spending on education and the literacy rate in South Africa; (b) while the long run effect of government education spending on literacy is not significant, there is a statistically significant positive effect in the short run. These findings have several implications for policymakers and other stakeholders. Therefore, the study recommends that increased monitoring and evaluation mechanisms are desirable in the primary and secondary education sectors for accountability and reducing wastage of taxpayer funds. The Department of Education is also encouraged to re-consider current teacher training practices and fill long standing vacancies in the school sector that negatively impact education outcomes.